2022
DOI: 10.1111/ppl.13685
|View full text |Cite
|
Sign up to set email alerts
|

Seedling‐stage salinity tolerance in rice: Decoding the role of transcription factors

Abstract: Rice is an important staple food crop that feeds over half of the human population, particularly in developing countries. Increasing salinity is a major challenge for continuing rice production. Though rice is affected by salinity at all the developmental stages, it is most sensitive at the early seedling stage. The yield thus depends on how many seedlings can withstand saline water at the stage of transplantation, especially in coastal farms. The rapid development of “omics” approaches has assisted researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 106 publications
(133 reference statements)
1
2
0
Order By: Relevance
“…ERF, MYB, bZIP, and WRKY are known for their contribution to stress tolerance [33]; their association with lncRNA showed their involvement in TFs-driven stress tolerance. A recently-published review by Tiwari et al [34] also reported the involvement of these TFs in salinity tolerance, particularly in the contrasting rice genotypes used in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…ERF, MYB, bZIP, and WRKY are known for their contribution to stress tolerance [33]; their association with lncRNA showed their involvement in TFs-driven stress tolerance. A recently-published review by Tiwari et al [34] also reported the involvement of these TFs in salinity tolerance, particularly in the contrasting rice genotypes used in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…Rhizospheric microbiomes heavily colonize the plant roots due to the availability of a nutrient-enriched biosphere comprising amino acids, carbohydrates, fatty acids, and organic acids acting as a passageway for the attraction of multiple microorganisms that thrive in this rhizosphere by utilizing root exudates. This dynamic zone around roots facilitates the microbial synthesis of compatible solutes, enzymes such as 1-aminocyclopropane-1-carboxylate (ACC) deaminase, and cell wall-degrading enzymes ions, as well as other secondary metabolites including phyto-hormones such as auxins, cytokinins, gibberellins, and ethylene, which augment plant growth and defense system under saline stress conditions ( Figure 4 ) ( Tiwari et al., 2022 ). Microbes reduce stress in plants by controlling nutritional and hormonal equilibrium and inducing systemic tolerance to stress ( Table 1 ) ( Kumawat et al., 2022c ).…”
Section: Rhizospheric Microbiome As a Salinity-alleviating Agentmentioning
confidence: 99%
“…The mechanisms of hydrogen sulfide‐mediated alleviation of salinity tolerance signaling cross talk with other signaling pathways are considered in the review by Srivastava et al (2022), while Verma et al (2022) discuss the literature concerning the role of AUXIN RESPONSE FACTORS (ARFs) in auxin‐mediated drought and salinity stress response. The approaches that have been used to identify the transcription factors with a potential role in salinity stress tolerance are presented in the review by Tiwari et al (2022), which also discusses the functions of key transcription factors families such as AP2/EREBP, bZIP, NAC, WRKY, MYB, and zinc finger proteins, in salinity tolerance in rice seedlings.…”
mentioning
confidence: 99%